Answer:
x = 2.25 y = 0.75
Step-by-step explanation:
2x = 9.5- 5
2x = 4.5
x = 4.5 ÷ 2
x = 2.25
know we now what is x so in the second one we evaluate x
3(2.25) + 5y = 10.5
6.75 + 5y = 10.5
5y = 10.5- 6.75
5y = 3.75
y = 3.75 ÷ 5
y = 0.75
that's it !
if you want to check your answer you can evaluate x and y so it will be like
2×2.25 + 5
= 4.5 + 5 = 9.5
and
3× 2.25 +5×0.75
= 6.75 + 3.75 = 10.5
First you collect the like term then variable one side coefficient one side and constant
Answer:
(4, 5 )
Step-by-step explanation:
x + y = 9 → (1)
x - y = - 1 → (2)
adding the 2 equations term by term will eliminate y
2x + 0 = 8
2x = 8 ( divide both sides by 2 )
x = 4
substitute x = 4 into either of the 2 equations and solve for y
substituting into (1)
4 + y = 9 ( subtract 4 from both sides )
y = 5
solution is (4, 5 )
You forgot to provide the slope but here is how you do this
the slope 5 = (y2 - y) / (x2 - x) but we know that (x2, y2) = (-10, -5)
=> (-5 - y) / (-10 - x) = 5 --- multiply both sides by (-10 - x)
=> (-5 - y) = 5 (-10 - x)
=> (-5 - y) = -50 - (5)x --- add +5 to both sides
=> -y = (-50 + 5) - (5)x --- multiply both sides -1
=> y = 5x + 45 --- this will be your equation.